A Local Governance Framework : Analysis of Political and Social Accountability - Haliza, Ahmad (2014)
The overview of this study is mainly focusing on the political and social accountability in local government. There is five main objectives were develop, (1) to evaluate general perspective towards Ipoh City Council (2) to identify Ipoh City Councils‟ role in involving the community in the programs (3) to evaluate Ipoh City Councils‟ services (4) to assess Ipoh City Councils‟ infrastructure arrangement and (5) to identify the best way to appoint the Councilors of Ipoh City Council. Ipoh City Council accountability evaluated in five (5) key areas which is general perspective, program, service, infrastructure and councilor. The data for this research were collected from two sources, namely primary sources and secondary sources. The quantitative technique using structured questionnaire was used in this study to solicit responses from respondents. This study involved two group of respondent consists of clients who deal with local government administration and local government management employee. A total of 150 employee and 150 client around Ipoh City Council were selected as respondents of this study. The methodology in this study implies the method of descriptive statistic involved frequency, percentage and mean. Based on the analysis, it was found that most of both employee and client are satisfied with local government performance to serve communities. Analysis shows positive feedback about how local government manage complaint, satisfied with the development and services and highly agree to implement electoral system for councilors and given training for them. However, some client show that they unsure about local government financial planning system, program conducted by local government, monitoring of infrastructure and either election of councilors transparent or otherwise. Through the results obtained, several recommendations were introduced to improve accountability mechanism at local government level in the future.